Fiscal reforms that work - McDermott, C. John (Economic issues, 1996)
Budget deficits (the yearly excess of government expenditures over revenues) and government debt (the deficits accumulated over the years) have soared in many industrial countries over the past 20 years, and almost all these countries are now faced with the challenge of bringing them back to earth. The present very serious problem of budget deficits and public debt has come about mainly because the growth in government spending has exceeded the growth of goods and services and has left groth in revenues trailing far behind. While the average ratio of tax revenue to GDP in industrial countries increased from 28 percent in 1966 to 44 percent in 1994 (the value of 44 percent of everything produced in one year in these countries went to taxes and fees), the corresponding ratio for government expenditures rose from 28 percent to 50 percent (the government spent the equivalent of half the value of all goods and services produced in a year). Given the high levels to which taxes have risen and the danger of stifling growth by raisin taxes further, to say nothing of the political consequences of trying to do so, it is reasonable to suppose that reducing government spending offers the best means, if not only means, of eliminating these fiscal imbalances.